Life Before "I Killed the Man That Raped Me": Pre-Prison Life Experiences of Incarcerated Women With Life Sentences and Subsequent Treatment Needs. Issue 1 (1st January 2018) - Fedock, Gina
Abstract : The number of incarcerated women serving a life sentence is growing. This subpopulation rarely receives programming in prison or even inclusion in intervention studies' samples. According to importation theory, characteristics of prisoners' pre-prison experiences guide the types of interventions provided to prisoners. This study examined the importation factors for a sample of women serving life sentences and used thematic analysis to understand these factors. The primary theme was the dominance of trauma in women's pre-prison lives with four connected sub-themes that highlight treatment needs pre-and during prison. One implication of this study is improving prison policies to include this subpopulation in treatment opportunities.